2022
DOI: 10.3389/fcvm.2022.845439
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Patients With Chronic Cardiovascular Disease During COVID-19 Lockdown

Abstract: ObjectivesThis cross-sectional study aims to investigate health-related behaviors including tobacco consumption among patients with cardiovascular diseases (CVD), during the first COVID-19-related lockdown.MethodsAfter 5 weeks of COVID-19 lockdown, 220 patients with chronic coronary syndromes (CCS) and 124 with congestive heart failure (CHF) answered a phone questionnaire.ResultsAmong these 344 patients, 43 (12.5%) were current smokers, and none had quit during the lockdown. When compared with non-smokers, smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The results clearly show a situation of underdiagnosis of T2D in the year 2020. This scenario of underdiagnosis has also been seen in other pathologies, such as cardiovascular disease ( 16 , 17 ) or buccal disorders ( 18 ), among others. In addition, in 2020 and 2021, subjects with T2D and dyslipidemia worsened their glucose and HbA1c levels and improved their lipid profiles, respectively, when compared to 2019.…”
Section: Discussionmentioning
confidence: 85%
“…The results clearly show a situation of underdiagnosis of T2D in the year 2020. This scenario of underdiagnosis has also been seen in other pathologies, such as cardiovascular disease ( 16 , 17 ) or buccal disorders ( 18 ), among others. In addition, in 2020 and 2021, subjects with T2D and dyslipidemia worsened their glucose and HbA1c levels and improved their lipid profiles, respectively, when compared to 2019.…”
Section: Discussionmentioning
confidence: 85%
“…According to Yan et al 3 and Sidor and Rzymski 16 , more than 45% and 74.1% of smokers, respectively, saw their frequency of consumption increase during confinement. Similarly, Klemperer et al 17 and Chagué et al 18 reported that 30% of respondents increased their consumption. The study carried out by the French public health authorities 19 on smoking behavior and trends, found that around 25% of smokers said they had increased their tobacco consumption; the same figure was reported by Cransac-Miet et al 20 .…”
Section: Dependencementioning
confidence: 87%
“…It is a concerning finding that individuals with co-morbid medical conditions were more likely to increase their smoking given their higher risk of more severe COVID-19 illness [ 49 ]. One potential explanation for this association is that those with medical conditions might have felt more stress and/or experienced greater mental health complications because of their medical status, which, in turn, promoted smoking [ 25 , 50 , 51 ]. Another possibility is that having a medical co-morbidity may be related to greater difficulty quitting smoking.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that the initial waves of the pandemic impacted tobacco use patterns in varied ways [ 17 ]. For instance, some adults endorsed increased tobacco use due to greater stress/negative effect [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Conversely, others reported decreased use because of reduced ability to afford or access tobacco products [ 26 , 27 ], lower social opportunities where use typically occurred [ 28 ] and/or health concerns [ 20 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%